Luaran Maternal dan Perinatal Kehamilan dengan HIV di RSUP dr. Kariadi Semarang Tahun 2019-2021 - Christian Agustin Tapa; M.Besari Adi Parmono; Setyo Gundi Pramudi; Ratnasari Dwi Cahyanti (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Human Immunodeficiency Virus (HIV) remains a global health crisis. HIV infection during pregnancy is associated with an increased risk of adverse maternal and perinatal outcomes.Objective: To determine the maternal and perinatal outcomes of HIV in pregnant women.Method: The descriptive study of pregnant women with HIV infection was done at Central General Hospital dr. Kariadi Semarang January 2019 – December 2021.Results and Discussion: From 122 cases of pregnancy with HIV infection, the majority of cases were found in 20-34 years old group (75,4%), finished high school education (51.6%), working as a housewife (55.7%), 37-41 weeks pregnancy (84.4%), primiparity (35.2%), mean frequency of antenatal care 5 (0-10), was diagnosed with HIV during the third trimester of pregnancy (27.9%), received ARV therapy during the third trimester (30.3%), history of drug withdrawal 13 cases, CD4 cell count 200-500 cells/mm3 (41.8%), hospital referral (47.5%), emergency referral (94.9%), cesarean section (95.9%), opportunistic infections (19.7%), and co-morbidities (56.6%). Maternal outcomes included preterm delivery (15.6%), premature rupture of membranes (PROM) (11.5%), and postpartum hemorrhage (0.8%), and there was no maternal mortality case. Perinatal outcomes included small gestational age (SGA) (30.3%), low birth weight (LBW) (21.3%), asphyxia (19.7%), and prematurity (15.6%). There were no perinatal deaths and fetal growth restrictions.Conclusion: The incidences of pregnancies with HIV infection in 2019-2021 were found in 122 cases. The most common maternal outcome was preterm delivery and PROM. The most common perinatal outcome was SGA, LBW, asphyxia, and prematurity. Keywords: HIV; maternal; outcomes; perinatal; pregnancy Abstrak Latar Belakang: Human Immunodeficiency Virus (HIV) masih menjadi krisis kesehatan global. Infeksi HIV pada ibu hamil memiliki hubungan dengan peningkatan risiko luaran maternal dan perinatal yang buruk.Tujuan: Mengetahui luaran maternal dan perinatal kehamilan dengan HIV.Metode: Penelitian deskriptif pada seluruh ibu hamil dengan HIV yang bersalin di RSUP dr. Kariadi Semarang Januari 2019 – Desember 2021.Hasil dan Pembahasan: Dari 122 kasus kehamilan dengan HIV, ibu hamil mayoritas berusia 20-34 tahun (75,4%), pendidikan terakhir SMA (51,6%), pekerjaan sebagai ibu rumah tangga (55,7%), usia kehamilan 37-41 minggu (84,4%), paritas primipara (35,2%), rata-rata frekuensi ANC yaitu 5(0-10), waktu terdiagnosis HIV pada trimester 3 (27,9%), terapi ARV dimulai pada trimester 3 (30,3%), riwayat putus obat 13 ibu, jumlah sel CD4 200-500 sel/mm3 (41,8%), asal rujukan rumah sakit (47,5%), rujukan kegawatdaruratan (94,9%), bedah sesar (95,9%), infeksi oportunistik (19,7%), dan penyakit penyerta (56,6%).  Luaran maternal meliputi persalinan prematur (15,6%), ketuban pecah dini (11,5%), perdarahan postpartum (0,8%) dan tidak ada kematian maternal.  Luaran perinatal meliputi kecil massa kehamilan (30,3%), berat badan lahir rendah (BBLR) (21,3%), asfiksia (19,7%), dan prematuritas (15,6%). Tidak ditemukan kematian perinatal dan pertumbuhan janin terhambat (PJT).Kesimpulan: Kejadian kehamilan dengan HIV tahun 2019-2021 adalah sebanyak 122 kasus. Luaran maternal terbanyak adalah persalinan prematur dan KPD, sedangkan luaran perinatal terbanyak adalah KMK, BBLR, asfiksia dan prematuritas. Kata kunci: HIV; kehamilan; luaran; maternal; perinatal